Identification of a respiratory-type nitrate reductase and its role for survival of mycobacterium smegmatis in wayne model - Khan, Arshad; Sarkar, Dhiman (Microbial Pathogenesis, 2006)
Nitrate reductase (NR) is found to be expressed in certain mycobacterium sp. whose link with the development of persistence is yet to be resolved. The present study demonstrates the action of selective inhibitors on NR as well as in the survival of Mycobacterium smegmatis using Wayne's model. During gradual shift down to anaerobic stage in Wayne's model, conversion of nitrate to nitrite became apparent in M. smegmatis. More than 97 percent inhibition was observed for the conversion of nitrate to nitrite by azide (0.05 mM) and thiocyanate (20 mM) in both whole-cell as well as its cell-free lysate, respectively. Under identical condition, chlorate (20 mM) inhibited nitrate reduction by 67 and 10 percent, respectively. At these concentrations, neither of azide, thiocyanate nor chlorate had any significant effect on cell growth under aerobic condition. In Wayne's culture model, thiocyanate and chlorate inhibited the growth of M. smegmatis by almost 2 logs at the same concentrations whereas azide inhibited by almost 1.75 log when added at the time of inoculation. Exposure of same culture at 96 h after inoculation in Wayne's model to these inhibitors showed 1.74, 1.95 and 2.37 log inhibition of viable cells with respect to azide, thiocyanate and chlorate. These findings further indicated that NR inhibitors kill the bacilli at anaerobic stage under the experimental condition mentioned. Metronidazole (MTZ) (2 mM) and Nitrofurantoin (NIT) (0.3 mM) reduced the cell number at both stages by < 0.7log. They did not have any effect on NR. Altogether, the results clearly indicate that NR-specific inhibitors could become more promising in killing the bacilli at anaerobic stage than the available conventional drugs. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Mycobacterium smegmatis; nitrate reductase; Wayne model

Bactericidal activity of 2-nitroimidazole against the active replicating stage of mycobacterium bovis BCG and mycobacterium tuberculosis with intracellular efficacy in THP-1 macrophages - Khan, Arshad; Sarkar, Sampa; Sarkar, Dhiman (International Journal of Antimicrobial Agents, 2008)
This study evaluated the antituberculous potential of 2-nitroimidazole under in vitro conditions. Minimal bactericidal concentrations of the compound against actively replicating Mycobacterium bovis BCG and Mycobacterium tuberculosis H37Ra were found to be 0.226 mu g/mL and 0.556 mu g/mL in enriched and minimal medium, respectively. Minimal inhibitory concentrations were > 100 times lower than reported antituberculous nitroimidazoles such as nitrofurantoin and furaltadone, indicating the greater potential of 2-nitroimidazole. No discernible effect of 2-nitroimidazole was seen on saprophytic Mycobacterium smegmatis and the representative bacterial strain Escherichia coli DH5 alpha, indicating the specificity of the molecule against tuberculous mycobacteria. The compound was also found to be effective against M. tuberculosis in the intracellular environment of the human monocytic cell line THP-1, with a reduction in viability of bacilli by 2.5 log after 144 h of incubation at a concentration of 0.113 mu g/mL. A five-fold higher concentration (0.565 mu g/mL) of 2-nitroimidazole sterilised the macrophages of intracellular pathogens within 192 h, without affecting the host. However, 2-nitroimidazole was unable to affect significantly the viability of dormant non-replicating bacilli of M. bovis BCG and M. tuberculosis in Wayne's in vitro model. Overall, the results indicate that 2-nitroimidazole is a potent antituberculous agent active against the organism's active replicating stage, with promising intracellular efficacy as well. (c) 2008 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 2-nitroimidazole; antimycobacterial agents; nitroimidazoles; THP-1 macrophage; tuberculosis

Presence of a functional nitrate assimilation pathway in mycobacterium smegmatis - Khan, Arshad; Akhtar, Shamim; Ahmad, Jawid N.; Sarkar, Dhiman (Microbial Pathogenesis, 2008)
Ability of Mycobacterium smegmatis to assimilate nitrate was evaluated in its active and dormant phase. Nitrate (10 mM), nitrite (0.5 mM) and ammonia (10 mM)allowed growth of M. smegmatis concomitant with their complete depletion from the culture in 144, 120 and 96 h, respectively, when used as sole nitrogen Source. Azide (50 mu M) stopped the growth of M. smegmatis when nitrate was used as sole nitrogen source. L-methionine-S-sulfoximine (L-MSO), which is a well-known inhibitor of glutamine synthetase, an enzyme also involved in nitrogen metabolic pathway, when applied at 10 mu g/ml concentration, completely inhibited the growth of the organism when nitrate or nitrite was used as sole nitrogen source. There was no effect of either azide or L-MSO at above concentrations on the growth of the organism when asparagine or ammonia was used as sole nitrogen source. More significantly, utilization of nitrate, nitrite and ammonia continued even in oxygen depletion induced dormant culture at the rates of 289, 25 and 354 mu M/day, respectively. These rates were 5-8 times slower than the rates of 1966, 127 and 2890 mu M/day, respectively, in active replicating phase. In the presence of azide (50 mu M) and L-MSO (10 mu g/ml), 2.1 and 1.51 logs reduction in viability of dormant M. smegmatis was observed using nitrate and nitrite, respectively, as sole nitrogen source. Altogether, the results indicated the presence of nitrate assimilation pathway operating in both active and dormant stage of M. smegmatis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Dormant bacilli; Glutamine synthetase; L-methionine-S-sulfoximine; Mycobacterium smegmatis; Nitrate assimilation

Simple whole cell based high throughput screening protocol using Mycobacterium bovis BCG for inhibitors against dormant and active tubercle bacilli - Khan, Arshad; Sarkar, Dhiman (Journal of Microbiological Methods, 2008)
This study aimed at developing a whole cell based high throughput screening protocol to identify inhibitors against both active and dormant tubercle bacilli. A respiratory type of nitrate reductase (NarGHJI), which was induced during dormancy, could reflect the viability of dormant bacilli of Mycobacterium bovis BCG in microplate adopted model of in vitro dormancy. Correlation between reduction in viability and nitrate reductase activity was seen clearly when dormant stage inhibitor metronidazole and itaconic anhydride were applied in this in vitro microplate model. Active replicating stage could also be monitored in the same assay by measuring the A(620) of the culture. MIC values of 0.08, 0.075, 0.3 and 3.0 mu g/ml, determined through monitoring A(620) in this assay for rifampin, isoniazid, streptomycin and ethambutol respectively, were well in agreement with previously reported by BACTEC and Bio-Siv assays. S/N ratio and Z' factor for the assay were 8.5 and 0.81 respectively which indicated the robustness of the protocol. Altogether the assay provides an easy, inexpensive, rapid, robust and high content screening too] to search novel antitubercular molecules against both active and dormant bacilli. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: high throughput screening; tuberculosis; Wayne's dormancy model; whole cell based assay

Nitrate reduction pathways in mycobacteria and their implications during latency - Khan, Arshad; Sarkar, Dhiman (Microbiology-SGM, 2012)
Mycobacterial persistence has gained a lot of attention with respect to developing novel antitubercular drugs, which could drastically reduce the duration of tuberculosis (TB) therapy. A better understanding of the physiology of Mycobacterium tuberculosis, and of the metabolic state of the bacillus during the latent period, is a primary need in finding drug targets against persistent TB. Recent biochemical and genetic studies of nitrate reduction in mycobacteria have revealed the roles of distinct proteins and enzymes involved in the pathway. The differential degree of nitrate reduction among pathogenic and non-pathogenic mycobacterial species, and its regulation during oxygen and nutrient limitation, suggest a link between nitrate reduction pathways and latency. The respiratory and assimilatory reduction of nitrate in mycobacteria may be interconnected to facilitate rapid adaptation to changing oxygen and/or nitrogen conditions, increasing metabolic flexibility for survival in the hostile host environment. This review summarizes the nitrate metabolic pathways operative in mycobacteria to provide an insight into the mechanisms that M. tuberculosis has evolved to adapt successfully to the host environment.

Nitrite reductase NirBD is induced and plays an important role during in vitro dormancy of mycobacterium tuberculosis - Akhtar, Shamim; Khan, Arshad; Sohaskey, Charles D.; Jagannath, Chinnaswamy; Sarkar, Dhiman (Journal of Bacteriology, 2013)
Mycobacterium tuberculosis is one of the strongest reducers of nitrate among all mycobacteria. Reduction of nitrate to nitrite, mediated by nitrate reductase (NarGHJI) of M. tuberculosis, is induced during the dormant stage, and the enzyme has a respiratory function in the absence of oxygen. Nitrite reductase (NirBD) is also functional during aerobic growth when nitrite is the sole nitrogen source. However, the role of NirBD-mediated nitrite reduction during the dormancy is not yet characterized. Here, we analyzed nitrite reduction during aerobic growth as well as in a hypoxic dormancy model of M. tuberculosis in vitro. When nitrite was used as the sole nitrogen source in the medium, the organism grew and the reduction of nitrite was evident in both hypoxic and aerobic cultures of M. tuberculosis. Remarkably, the hypoxic culture of M. tuberculosis, compared to the aerobic culture, showed 32- and 4-fold-increased expression of nitrite reductase (NirBD) at the transcription and protein levels, respectively. More importantly, a nirBD mutant of M. tuberculosis was unable to reduce nitrite and compared to the wild-type (WT) strain had a >2-log reduction in viability after 240 h in the Wayne model of hypoxic dormancy. Dependence of M. tuberculosis on nitrite reductase (NirBD) was also seen in a human macrophage-based dormancy model where the nirBD mutant was impaired for survival compared to the WT strain. Overall, the increased expression and essentiality of nitrite reductase in the in vitro dormancy models suggested that NirBD-mediated nitrite reduction could be critical during the persistent stage of M. tuberculosis.

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis